A collaborative planning process to develop future scenarios for wastewater systems. (15th August 2022) - Neth, Maria; Mattsson, Ann; I'Ons, David; Tumlin, Susanne; Arnell, Magnus; Blom, Lena; Wilén, Britt-Marie; Modin, Oskar
Abstract: Wastewater infrastructure has a long lifetime and is subject to changing conditions and demands. When plans are made to upgrade or build new infrastructure, transdisciplinary planning processes and a robust analysis of future conditions are needed to make sustainable choices. Here, we provide a stepwise collaborative planning process in which future scenarios are developed together with local stakeholders and expert groups. The process was implemented at one of the largest wastewater treatment plants (WWTPs) in Scandinavia. With a combination of workshops and the use of a web-based digital tool, future scenarios including flows, pollutant loads, and treatment requirements could be created. Furthermore, sustainability prioritizations affecting the WWTP, were identified. The future scenarios developed for the WWTP in the case study, predict stricter and new regulations, constant or lower future loads and ambiguous future flows. The highest ranked sustainability priority was low resource and energy consumption t ogether with low CO2 footprint. The quantified future scenarios developed in the planning process were used as input to a process model to show the consequences they would have on the WWTP in the case study. Applying this collaborative process revealed future scenarios with many, sometimes conflicting, expectations on future WWTPs. It also highlighted needs for improvements of both the collection system and the WWTP. Graphical abstract: Image 1 Highlights: A process involving stakeholders and experts to build future scenarios was developed. Simulating future scenarios showed potential impacts and needs for upgrade. Sustainability priorities were predicted. New and stricter requirements on future WWTPs were predicted. Future scenarios revealed conflicting expectations on future WWTPs.